Estratégia saúde da família no município de Franca-SP: a visão do usuário e a relação com a promoção da saúde - Sandoval, Eduardo Guerra Barbosa (2009)
Introduction: Family Health Strategy aims to open up accessibility to basic healthcare services, seeking the available technologies for promotion, prevention and healthcare used with equity. The users’ expectations should be considered regarding these three dimensions that characterize the model of basic care proposed within Family Health Strategy. General Objective: delineate the resident population in one of the boroughs covered by the Family Health program, in the Municipality of Franca, and identify its link to and its expectations in relation to the Family Health Center. The borough studied is called Jardim Palma. Method: A descriptive, transversal study was carried out with a random sample of the resident population in the area covered by the Family Health Center in the Jardim Palma borough in the City of Franca. Ninety-nine of the 1070 homes that compose the borough were contacted and questionnaires were filled out with a member of a family group within each domicile. This procedure collected information from a total of 365 dwellers. Results: 77.8% of the families were registered at the Palma Family Health Center; 80% of those interviewed already had been attended at the Center, with the more frequent type of attendance being a medical appointment (68.7%); 30.3% of the families have a health plan, and 21.3% of these have already been attended by the Center. As an alternative to the services offered by the Center, 39.4% of those interviewed had procured the Municipal Emergency Room and 13.1% private medical practice; 63.6% of those interviewed said that the Palma Center needed improvements; 29.3% wanted more doctors and 16.2% thought that there should be more specialists in the Center. Conclusion: The population uses the Center more often for doctor appointments, without demanding any activities concerning health promotion. Even those people that have alternatives in medical assistance use the Center for regular outpatient care. The expectations of an increase in the number of doctors and the addition of specialists suggest that Family Health Strategy still needs adjustments and better orientation to consolidate itself as a model for Basic Assistance which incorporates Health Promotion.